Proposal of framework to managing the automotive product development process. Issue 1 (1st January 2017) - Canuto da Silva, Guilherme; Kaminski, Paulo Carlos
Abstract: This paper aims to propose a framework to managing the automotive product development process. The framework, named as Automotive-PDP, was developed through a bibliographical survey and through a study of three global automakers from Asia, Europe and America. In order to verify the Automotive-PDP acceptance, interviews involving 75 professionals from automakers, auto parts and automotive design companies were performed. The goal of these interviews was to verify the practice use of the framework (Automotive-PDP) in the automotive sector. The framework development is presented and the findings from interviews are showed. Afterwards, the paper is finished with the relevant conclusions.